Optimizing The Utilization of Arabica Coffe Grounds Extract on the Growth Perfomance of Tilapia (Oreochromis Niloticus) - Nisa, Haerunnisaa; Diamahesa, Wastu Ayu; Lestari, Dewi Putri (Jurnal Biologi Tropis, 2024)
Nile tilapia (Oreochromis niloticus) is a widely cultivated freshwater fish due to its adaptability to various environments and ease of breeding. Feed availability is a crucial factor in the success of tilapia cultivation. Quality feed plays a vital role in fish development and using effective feed management strategies can help reduce costs and improve growth outcomes. Previous studies have suggested that coffee grounds can enhance fish immunity and growth due to their antioxidant properties. This research aimed to investigate the impact of adding coffee grounds to commercial feed on the growth and survival of Nile tilapia. The study was conducted over 45 days using a completely randomized design with five treatments and three replications. Treatments included a control group (P1) and feed supplemented with 0.5g (P2), 1g (P3), 3g (P4), and 5g (P5) of coffee grounds per 100g of feed. The results indicated that the addition of coffee grounds significantly affected weight growth, with the highest growth observed in P5. However, no significant differences were found in length growth or specific growth rate (SGR) among treatments. Feed consumption was highest in P2, but feed conversion ratio (FCR) and feed utilization efficiency were most favorable in P5. Water quality parameters remained within optimal ranges throughout the study.